STUDENTS’ WRITING ANXIETY IN ACADEMIC WRITING PRACTICE - Desfi Yenti; Roza Susanti (ELP (Journal of English Language Pedagogy), 2025)
Writing in academic English can be challenging, often leading to feelings of nervousness and hesitation among students. This study aims to identify the types of writing anxiety experienced by English Department students during academic writing. Twenty undergraduate students from STKIP Yayasan Abdi Pendidikan Payakumbuh participated in the research. Data were collected using the Second Language Writing Anxiety Inventory (SLWAI) developed by Chang, which consists of closed-ended questions and is classified as a standardized questionnaire. The findings indicate that cognitive anxiety is the most prevalent form of writing anxiety among students. This reinforces the notion that writing anxiety is a significant barrier to developing writing skills, consistent with similar research conducted at other universities. To enhance their writing success, students must consider several important factors, including personality traits, teaching methods, awareness, and emotional influences. Future research should further explore these variables, as understanding their impact can lead to improved teaching practices and better support for students facing writing anxiety. By addressing these factors, educators can create a more conducive learning environment that fosters confidence and skill development in academic writing. Ultimately, recognizing and mitigating writing anxiety is essential for helping students succeed in their academic endeavors.